New method for coupled fluid-structure interaction problems in biomechanics - Farnell, D. J. J.; David, T.; Barton, D. C. (ISB Congress, 2005)
A novel method has been developed for numerically simulating coupled fluid-structure interaction problems in nature. The method has been applied to several problems, including heart valve dynamics and the swimming action of certain fish, and shown to be robust, efficient and reliable. In principle, it will be possible to extend the method to other problems (e.g. retinal tears in the posterior chamber of the eye) and to fully three-dimensional analysis.